Increased collection efficiency of CD34+ cells after mobilization with preemptive use of plerixafor followed by leukocytapheresis on the same day. Issue 4 (17th February 2020) - Cid, Joan; Castillo, Carlos; Marín, Pedro; Carbassé, Gloria; Herrera, Dolores; Monfort, Nuria; Fernández‐Avilés, Francesc; Gutiérrez‐García, Gonzalo; Martínez, Carmen; Rosiñol, Laura; Suárez‐Lledó, María; Rovira, Montserrat; et al.
Abstract : BACKGROUND: Plerixafor should be administered 6 to 11 hours before starting leukocytapheresis. However, we have been using plerixafor followed by leukocytapheresis according to different time schedules since 2007. Our objective was to compare the CD34+ cell collection efficiency (CE1) of the first leukocytapheresis performed after using plerixafor at different time intervals. STUDY DESIGN AND METHODS: Same‐day schedule refers to the administration of plerixafor at 10:00 AM and starting the leukocytapheresis on the same day at 4:00 PM (6 hours interval). Next‐day schedule refers to the administration of plerixafor at 8:00 PM and starting the leukocytapheresis on the next day (10:00 AM or 4:00 PM; either a 14‐ or 20‐hr interval). Variables that might influence the CE1 of CD34+ cells were analyzed by longitudinal linear regression with a random effects model derived by generalized estimating equations. RESULTS: The median CE1 of CD34+ cells was higher in the group of 30 patients who underwent leukocytapheresis on the same day when compared with the group of 62 patients who underwent leukocytapheresis on the next day (65.8% vs. 56.7%; p < 0.01). In the longitudinal linear regression analysis, only the time from plerixafor administration to leukocytapheresis start was associated with a statistically significant decrease in the CE1 of CD34+ cells (CE1 change −0.034%; p < 0.01). CONCLUSION: Higher CE1 of CD34+ cells was observed when patients underwent leukocytapheresis on the same day after receiving plerixafor in comparison with administering plerixafor and underwent leukocytapheresis on the next day. Larger studies are necessary to confirm present results.